1987
DOI: 10.2214/ajr.148.3.479
|View full text |Cite
|
Sign up to set email alerts
|

Urography and voiding cystourethrography: findings in girls with urinary tract infection

Abstract: The voiding cystourethrogram and excretory urogram have been considered essential parts of the evaluation of girls with urinary tract infections. To evaluate the usefulness of these procedures, 523 examinations in girls with urinary tract infections were reviewed retrospectively.The major finding on voiding cystourethrograms was vesicoureteral reflux, occurring in 36% of the children. Of the total group, 8% had excretory urographic evidence of parenchymal scarring.Higher grades of reflux were associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
4

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 0 publications
1
9
1
4
Order By: Relevance
“…In this condition, which occurs in 30% to 40% of children who have had a UTI, 9 urine flows backward toward the kidneys during bladder contraction. VUR is associated with an increased risk of recurrent UTI and renal scarring, [10][11][12] but it is neither necessary nor sufficient for either of these outcomes. 3,[13][14][15][16][17] In recent years, there has been increased appreciation that other factors, such as bladder and bowel dysfunction (BBD) 18 and defects in innate immunity, 19,20 may also be important contributors to the recurrence of UTI.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In this condition, which occurs in 30% to 40% of children who have had a UTI, 9 urine flows backward toward the kidneys during bladder contraction. VUR is associated with an increased risk of recurrent UTI and renal scarring, [10][11][12] but it is neither necessary nor sufficient for either of these outcomes. 3,[13][14][15][16][17] In recent years, there has been increased appreciation that other factors, such as bladder and bowel dysfunction (BBD) 18 and defects in innate immunity, 19,20 may also be important contributors to the recurrence of UTI.…”
Section: What This Study Addsmentioning
confidence: 99%
“…11,12 The basis for this VUR screening and treatment strategy is a theoretical model that links VUR to an increased risk of recurrent UTI and renal scarring. [13][14][15] However, there is a paucity of evidence for this model, 9 and recent small clinical trials evaluating the efficacy of prophylaxis have demonstrated no protective effect for preventing recurrent UTI and renal scarring. 5,16 Moreover, concerns have been raised about the potential harm of antimicrobial prophylaxis because of its potential to breed resistant organisms that can cause recurrent UTIs.…”
Section: Stimates Of Cumulative Inci-mentioning
confidence: 99%
“…10 Voiding urethrocystography assesses the anatomy of the urinary bladder and urethra, and the presence of vesicoureteral reflux. 11 Radioisotopic cystography is used in the follow-up of vesicoureteral reflux. Renal scintigraphy provides information about the renal function and anatomy.…”
Section: Materials a N D Methodsmentioning
confidence: 99%